THE TRAINING AND ASSISTANCE OF MOCAF FLOUR PRODUCTION AS A SMALL COMMUNITY INDUSTRY TO INCREASE FAMILY INCOME AND ECONOMIC COMMUNITY - Mubarokah, Syaima Lailatul (Qardhul Hasan: Media Pengabdian kepada Masyarakat, 2015)
In the districts, especially in the village Citapen Ciawi there are some cassava farmers who have not been able to make cassava into refined products, namely flour mocaf seed. By holding the training and marketing of mocaf flour production, the public will be able to establish a small industry of flour in order to increase farmers' income by producing quality products in the long term. The method used in the training were started the promotion to KWT Pillars Citapen Tani village and then trained of the production and marketing of flour mocaf and its processed products. Production and marketing of training mocaf flour had a positive impact on the change in condition of the community, building the creative society, science and the experience gained and revenue increases seen by the data obtained from the public respondents.